Visceral leishmaniasis and HIV coinfection in Latin America. - José Angelo Lindoso; Gláucia Fernandes Cota; Alda Maria da Cruz; Hiro Goto; Ana Nilce Silveira Maia-Elkhoury; Gustavo Adolfo Sierra Romero; Márcia Leite de Sousa-Gomes; Joanna Reis Santos-Oliveira; Ana Rabello (Public Library of Science (PLoS), 2014)
Visceral leishmaniasis (VL) is an endemic zoonotic disease in Latin America caused by Leishmania (Leishmania) infantum, which is transmitted by sand flies from the genus Lutzomyia. VL occurs in 12 countries of Latin America, with 96% of cases reported in Brazil. Recently, an increase in VL, primarily affecting children and young adults, has been observed in urban areas of Latin America. The area in which this spread of VL is occurring overlaps regions with individuals living with HIV, the number of whom is estimated to be 1.4 million people by the World Health Organization. This overlap is suggested to be a leading cause of the increased number of reported VL-HIV coinfections. The clinical progression of HIV and L. infantum infections are both highly dependent on the specific immune response of an individual. Furthermore, the impact on the immune system caused by either pathogen and by VL-HIV coinfection can contribute to an accelerated progression of the diseases. Clinical presentation of VL in HIV positive patients is similar to patients without HIV, with symptoms characterized by fever, splenomegaly, and hepatomegaly, but diarrhea appears to be more common in coinfected patients. In addition, VL relapses are higher in coinfected patients, affecting 10% to 56.5% of cases and with a lethality ranging from 8.7% to 23.5% in Latin America, depending on the study. With regards to the diagnosis of VL, parasitological tests of bone marrow aspirates have proven to be the most sensitive test in HIV-infected patients. Serologic tests have demonstrated a variable sensitivity according to the method and antigens used, with the standard tests used for diagnosing VL in Latin America displaying lower sensitivity. For this review, few articles were identified that related to VL-HIV coinfections and originated from Latin America, highlighting the need for improving research within the regions most greatly affected. We strongly support the formation of a Latin American network for coinfections of Leishmania and HIV to improve the consistency of research on the current situation of VL-HIV coinfections. Such a network would improve the collection of vital data and samples for better understanding of the clinical manifestations and immunopathogenic aspects of VL in immunosuppressed patients. Ultimately, a concerted effort would improve trials for new diagnostic methodologies and therapeutics, which could accelerate the implementation of more specific and effective diagnosis as well as public policies for treatments to reduce the impact of VL-HIV coinfections on the Latin American population.